PENGARUH NET PROFIT MARGIN, TOTAL ASSET TURNOVER DAN DEBT TO EQUITY RATIO TERHADAP PERTUMBUHAN LABA PADA SUB SEKTOR TEKNOLOGI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021 – 2023 - Pujianti, Putri; Nasution , Shabrina Tri Asti; Lores, Linda (Gapenas Publisher, 2025)
The study was conducted to find out the impact of Net Profit Margin, Total Asset Turnover and Debt To Equity Ratio on profit growth in technology sub-sector companies listed on Indonesian Stock Exchange 2021-2023. The kind of quantitative research with The causal associative approach. Total population of 47 technology sector companies with purposive techniques sampling of 13 companies over a three-year period with 39 data sets. Technically processing using double linear regression analysis. Research shows that by Partial net profit margins have an impact on earnings growth, total asset turnover has a significant effect on earnings gains and debt to equity ratio does not affect or are insignificant in earnings growth. At the same time, net profit margin, total asset turnover and debt to equity ratio have a significant positive impact on earnings growth.